THE ROLE OF BOLUGO VILLAGE OWNED BUSINESS ENTITY (BUM DESA) BOLUGO IN TOURISM DEVELOPMENT IN EAST BOROKO VILLAGE, KAIDIPANG DISTRICT NORTH MONGONDOW BOLAANG - Sarwo Eddy Posangi; Ikram Muhammad; Ismail Tahir (Journal of Economic, Business, and Administration (JEBA), 2024)
This research aims to: 1) Evaluate the role of Bolugo Village-Owned Enterprises (BUMDes) in developing village tourism in East Boroko Village, Kaidipang District, North Bolaang Mongondow Regency; 2) Identify the determinant factors influencing the performance of BUMDes in this sector. This study employs a qualitative approach with an intrinsic case study design. Data were collected through field observations, documentation, and structured interviews with key informants, including BUMDes managers and village officials. The results indicate that the role of BUMDes Bolugo in tourism development is currently suboptimal. This ineffectiveness is driven by a lack of community empowerment, the absence of strategic partnerships with higher education institutions, and the continued reliance on traditional, non-digital promotional methods. Furthermore, the study identifies facility development, inconsistent local government support, and the lack of benchmarking (orientation studies) as the primary determinant factors hindering tourism acceleration. The findings suggest that a shift toward participatory governance and digital integration is required to revitalize the village’s coastal tourism potential.